Effects of Cadmium on Germination and Biomass in Sugarcane Varieties of the Lower Guayas Basin (Revista Científica Ciencias Naturales y Ambientales, 2019)
The aim of this research was to evaluate the effects of cadmium on the germination and biomass of four varieties of sugarcane from the lower basin of the Guayas river, in order to propose a modification in the maximum allowable limit of cadmium in soils cultivated with this specie. Samples of the varieties Ragnar, ECU-01, CC 85-92 and CC-22 were exposed to growth during 21 days in a contaminated environment with five concentrations of cadmium (0.5, 1, 2, 4 y 8 mg/L). Cadmium did not have effects on germination. Radicles of the Ragnar, ECU-01 and CC-22 varieties were significantly affected in all the treatments, while the hypocotyls showed affectation in the treatments of 2 and 8 mg/L in ECU-01 and 2 mg/L in CC-22. The biomass was affected only in the ECU-01 variety, where the treatment of 2 mg/L caused a reduction of 51 % on it. The phytotoxicity integral index evidenced that the heavy metal was toxic in all the treatments of the four varieties; on the other hand, the tolerance index proved that CC 85-92 variety was the most tolerant, while ECU-01 was less tolerant to the effects of cadmium. Finally, the tolerance index and the biomass of seedlings exposed to experimentation with 0.25 mg/L, showed that to this concentration none of the varieties of sugarcane were affected significantly, so, that concentration can be considered as the maximum allowable limit in soils cultivated with the specie Saccharum officinarum.
Keywords: Sugarcane; Tolerance index; Phytotoxicity integral index; Radicles; Hypocotyls